2015
DOI: 10.17152/gefad.43887
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının “Bilgisayar” Kavramı Konusundaki Bilişsel Yapılarının Belirlenmesi

Abstract: ÖZ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 34 publications
0
9
0
4
Order By: Relevance
“…In the research, the evaluation and interpretation process of the metaphors indicated by the sports managers by content analysis was done in 9 stages in total. These are (1) examination of forms, (2) elimination of unsuitable forms, (3) recompilation of forms, (4) numbering forms (5) examination of metaphors, (6) development of categories, 7 stage of ensuring validity and reliability, (8) calculation of frequencies of obtained metaphors and (9) the interpretation of metaphors (Ekici, Baş & Kızılkaya, 2017;Ekici, 2016;Ekici, Gökmen & Kurt, 2014;Saban, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the research, the evaluation and interpretation process of the metaphors indicated by the sports managers by content analysis was done in 9 stages in total. These are (1) examination of forms, (2) elimination of unsuitable forms, (3) recompilation of forms, (4) numbering forms (5) examination of metaphors, (6) development of categories, 7 stage of ensuring validity and reliability, (8) calculation of frequencies of obtained metaphors and (9) the interpretation of metaphors (Ekici, Baş & Kızılkaya, 2017;Ekici, 2016;Ekici, Gökmen & Kurt, 2014;Saban, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The process of evaluation and interpretation of the metaphors, which the participants indicated in the research, by content analysis was done in 8 steps in total. These are (1) examination of forms and elimination of inappropriate forms, (2) recompilation of forms, (3) numbering forms (4) examination of metaphors, (5) development of categories, (6) the stage of providing validity and reliability, (7) calculation of frequencies of obtained metaphors, and 8interpretation of metaphors (Ekici, 2016;Ekici, Gökmen and Kurt, 2014;Saban, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Content analysis was carried out in 8 stages. These are (1) examination of forms and elimination of inappropriate forms, 8interpretation of metaphors (22,23,24).…”
Section: Methodsmentioning
confidence: 99%